The study on level of awareness among the muslim residents of taman Puchong Perdana, Selangor on the existence of Penolong Amil Kariah (PAK) of Masjid As-Salam / Muhammad Nurirsyad Ismail - Ismail, Muhammad Nur Irsyad (2019)
The main purpose of this exploratory study is to identify the level of awareness of Muslim residents and investigating if any factors (social involvement, rules and services of Penolong Amil Kariah ) influencing the awareness towards awareness among the Muslim residents of Taman Puchong Perdana, Selangor on the existence of Penolong Amil Kariah (PAK) of Masjid As- Salam. This study applies quantitative approach with the use of survey questionnaires as the main instrument of data collection. A total of 50 respondents were selected for the purpose of this study. Data collected was analysed using descriptive analysis, Pearson Correlation Coefficient, and Reliability analysis. In general, findings of this study show that relatively, the level of awareness towards retirement planning is moderate high but the knowledge Muslim residents about rule and services Penolong Amil Kariah is still low. Overall, this study gives some information on the awareness towards Muslim Residents Taman Puchong Perdana, Selangor on the existence Penolong Amil Kariah (PAK) of Masjid As-Salam.